Right to privacy and protection of personal data in the age of the COVID-19 pandemic - Čović, Ana (Sociološki pregled, 2020)
During the COVID-19 virus pandemic, individuals and society as a whole faced primarily challenges in the field of health, physical and mental, but also a number of other problems caused by the virus and various measures mainly related to restriction of freedom of movement and freedom of assembly. Apart from the health aspects of the global pandemic and its impact on the world economy, the sociological and legal aspects are extremely important, especially in the field of respect and protection of guaranteed human rights as one of the basic postulates of modern democratic society. When and to what extent their restriction is justified and expedient, as well as the exact limits of action of the state government and its representatives in situations when they are obliged to protect the general safety and public health of the population, are issues that have always caused numerous controversies and conflicting opinions. Today, individuals, various nongovernmental, regional and world organisations, are trying to answer the question whether during the past period man as a central subject of legal protection was seen through the eyes of respect, compassion and love of those whom he entrusted to make decisions on his behalf or whether the human dignity or a free man was sacrificed for the sake of political and financial interests of individuals and certain interest groups. Life in the digital era and the accelerated development of digital technologies have made the issue of privacy and personal data protection topical, especially in the period of the last global pandemic and the appearance of mobile applications for monitoring the contacts of patients. This raised the question of compliance of their use with legal regulations at the international and national level in the field of human rights protection.